The driving mechanism and path selection of green development in Chinese cities - Xisha, Wang; Jinye, Li (Frontiers in Environmental Science, 2023)
Green is the background color of high-quality urban development, by constructing a theoretical model based on the "three forces" and taking the "three drivens" as the content, this paper analyzes the driven force and driving mechanism of urban green development in China. According to the panel data of Chinese cities from 2010 to 2020, the green development path of Chinese cities is simulated. The empirical results show that the pulling force formed by scientific and technological innovation, the action force formed by structural adjustment and the propulsive force formed by environmental regulations drive Chinese cities to achieve green development. The comprehensive driven path formed by the combination of innovation driven, structure driven and environment driven is a better path for China's urban green development. Therefore, the green development of Chinese cities needs to increase investment in science and technology, guide all entities to develop in the direction of resource conservation and pollution reduction, adjust the industrial structure, promote their development in the direction of cleanliness, increase environmental protection investment, standardize the development of all entities in the direction of environmental protection, and give full play to the synergy of the three major policies to achieve green development.